(3EYLGR GdbQBfs - (3eMeO Hf GdWjH Hf eMeO Hf LYaQ, Jbj GdOjf CHh HcQ, GdbGVj GdHGbdGfj , J (B403 (3g` s ((3MSf Gdajhei s)
(3ChdgG (B:s
(3GdMeO ddg GdefYe Ydi YHGOg eeG gOGge Edjg ef GdEjeGf GdPi MeO faSg HeG GfRd ef GdbQBf s
(3BNQgG (B:s
(3hGSJQTOJ jQTOc hgh MSHi hMSHc hfYe Gdhcjd Je GdGYLGR s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B120s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JaSjQ (B347) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs